Assessment of Distance from Apical Foramen and Apical Constrictions to Root Apex of Maxillary and Mandibular Permanent Anterior Teeth among Bangladeshi National - Nabi, Md Noor; Akter, Khaleda; Nahar, Raihana; Hossain, Mohammad Tofazzel; Hasan, Md Ishtiaq; Hossain, Mozammal (Update Dental College Journal, 2025)
Background: Knowledge of apical anatomy is crucial in performing endodontic treatment. There are inconsistencies in the reported incidence of multiple foramina in single-rooted teeth. This could be due to the variations in investigative techniques, non-uniform terminology and the lack of agreement in distinguishing between apical and lateral foramina and the races. Therefore, the study was aimed to determine the distance from root apex to apical foramen, and root apex to apical constriction. Methods: A total of 132 anterior teeth consisting of 66 maxillary and 66 mandibular center incisor, lateral incisor and canine were selected. Periodontal tissue remnants were mechanically removed and teeth were stained with marker. The teeth were dried and examined using a Leica®EZ4E with 10× eye pieces 4.4:1 zoom stereomicroscope with digital camera. The distance from the anatomical apex of the tooth was measured by using stage micrometer and image J software. Statistical analysis between root apex morphology between the mandible and maxillary anterior teeth was performed by SPSS and differences between the groups were calculated by Chi square and student-t test; a value of p <0.05 was considered as statistically significant. Results: The results found that the distance between apical constrictions to root apex was 0.96 to 1.11 mm. Conclusion: There is no difference between maxillary and mandibular anterior teeth in respect to apical foramen and apical constrictions to root apex. Update Dent. Coll. j: 2025; 15(1): 33-36